Ratio Decidendi of Judges Decisions on Grondkaart Land Disputes in Indonesia - Masykur, Mohammad Hamidi; Khoironi, Moh. Lu'ay; Jimmy Firmansyah; Apriyas Munik (Pandecta Research Law Journal, 2024)
The impact of the existence of Grondkaart Land throughout Indonesia in its development has led to conflicts that can be classified into 4 (four): first, between the community and PT KAI; second, Indigenous people with PT KAI; third, City/Regency Government with PT KAI; and fourth, Sultanate/Palace with PT KAI. In general, community members who have controlled and utilised the Grondkaart land for many years feel they have the right to apply for property rights to the local Land Office.  Meanwhile, PT KAI continues to maintain that these lands are legitimate PT KAI assets based on the history of the Indonesian Nation which gave birth to the Land Map or Grondkaart as evidence of land control instructions by PT KAI. in this research, a normative juridical research method is used by using several approaches, namely the Statute Approach (Legislation Approach), Conceptual Approach (Concept Approach), Case Approach (Case Approach), and Comparative Approach (Comparative Approach) by using descriptive analytical methods that aim to describe precisely. From this, it causes a lawsuit in court as the final estuary where to seek justice, but the Court Institution which is expected to be a place to find justice actually has a difference in views / Disparity between Judges in viewing Grondkaart Land evidence so as to cause legal uncertainty. From this legal uncertainty